Optimal estimate of the convergence rate of statistic ρN = |ZNWN| - Vilkas, Robertas; Aksomaitis, Algimantas (Lietuvos matematikos rinkinys, 2003)
The optimal estimate of the convergence rate of distribution function of statistic ρN is given (for one of the examples in [1]) and unimprovable constants were obtained. Besides, the optimal non-uniform estimate from the right was found together with the unimprovable constant.